Potential use of silicon carbide monolayer as an anode in rechargeable Mg-ion batteries. (June 2023) - Kadhim, Mustafa M.; Taban, Taleeb Zedan; Abdullaha, Sallal A.H.; Rheima, Ahmed Mahdi; Hachim, Safa K.; Abed, Azher M.
Abstract: In this study, we evaluated the possible application of a two-dimensional silicon carbide monolayer, which is a similar to material graphene, as an anode material in rechargeable Mg-ion batteries based on density functional theory computations. In particular, we investigated the related electronic structures, structural geometry changes, Mg-ion diffusion characteristics, and the corresponding electrochemical characteristics during charging. The adsorption energy of Mg is higher on the six-ring member than other sites. The maximum theoretical capacity of SiC is as high as 683.99 mAh/g, which is accompanied by a negligible change in the Si–C spacing band. We also considered the changes in the open circuit voltage caused by the adatom concentrations due to the intercalation of Mg in Si. The open-circuit voltage range determined for the SiC monolayer after the adsorption of Mg adtoms also indicates that the SiC monolayer can be considered a promising anode material. Considerable charge transport of approximately one electron occurs in SiC nano-sheets from the Mg atom-, thereby making them electrically conductive, which is a requirement for an acceptable anode material. Furthermore, the SiC monolayer can be regarded as the best candidate for use as an anode material in magnesium-ion batteries because of its properties. Highlights: The adsorption energy of Mg enhances around the six-member ring in SiC. After Mg adsorption, SiC becomes electrically conductive. The diffusion of Mg on the Si–C bond is easier than in other directions.